Pengaruh Technological Pedagogical Knowledge (TPK) Guru Terhadap Pembelajaran Daring Di SD Budi Luhur Karang Tengah - Wahyu Ainun Habibah; Ainur Rosyid (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2021)
This study aims to determine the effect of teacher TPK variables on online learning at SD Budi Luhur. This research method uses a quantitative approach with a survey method. The data collection technique used a questionnaire with saturated sampling, with a sample size of 30 teachers. The calculation results obtained of 0.958 with a partial test (t test) obtained t count = 2.128> t table = 2.048 with a significance of 0.000 <0.05, meaning that is rejected and is accepted with a correlation coefficient of 42.6% indicating that the TPK of the teacher contributes to Online learning is high and the coefficient of determination is 43%, the remaining 57% is influenced by other factors. Based on these data, it means that there is a positive and significant relationship with the TPK teacher variable with online learning variables